1988
DOI: 10.1073/pnas.85.10.3289
|View full text |Cite
|
Sign up to set email alerts
|

Separation of positional isomers of oligosaccharides and glycopeptides by high-performance anion-exchange chromatography with pulsed amperometric detection.

Abstract: High-performance anion-exchange (HPAE) chromatography under alkaline conditions (pH~=13) has been found to efficiently separate neutral oligosaccharides (triose to undecaose) according to molecular size, sugar composition, and linkage of monosaccharide units. The method was able to resolve 1 -* 3, 1 -> 4, and 1 -* 6 positional isomers of neutral oligosaccharides, which are dermed as having the same number, type, sequence, and anomeric configurations of monosaccharides but differing in the linkage position of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(64 citation statements)
references
References 25 publications
0
64
0
Order By: Relevance
“…One method relied on electrochemical detection of native, released glycans after separation at high pH: high-performance anion exchange chromatography with pulsed amperometric detection (HPAEC-PAD). 28,[39][40][41][42] All other methods applied fluorescent labeling. Four methods used electrophoretic separation, which included conventional high-resolution capillary gel electrophoresis with laser-induced fluorescence [CE-LIF(APTS-HR1)], [43][44][45][46][47][48] DNA-sequencer-aided fluorophore-assisted carbohydrate electrophoresis after 8-aminopyrene-1,3,6-trisulfonic acid (APTS) labeling for high-throughput screening [DSA-FACE(APTS)], [49][50][51][52][53][54] high-resolution capillary gel electrophoresis with rapid labeling with APTS via reductive amination [CE-LIF (APTS-HR2)], and cartridge-based capillary gel electrophoresis with rapid 8-aminonaphthalene-1,3,6-trisulfonate (ANTS) labeling, in development specifically for screening [CCGE(ANTS)].…”
Section: Resultsmentioning
confidence: 99%
“…One method relied on electrochemical detection of native, released glycans after separation at high pH: high-performance anion exchange chromatography with pulsed amperometric detection (HPAEC-PAD). 28,[39][40][41][42] All other methods applied fluorescent labeling. Four methods used electrophoretic separation, which included conventional high-resolution capillary gel electrophoresis with laser-induced fluorescence [CE-LIF(APTS-HR1)], [43][44][45][46][47][48] DNA-sequencer-aided fluorophore-assisted carbohydrate electrophoresis after 8-aminopyrene-1,3,6-trisulfonic acid (APTS) labeling for high-throughput screening [DSA-FACE(APTS)], [49][50][51][52][53][54] high-resolution capillary gel electrophoresis with rapid labeling with APTS via reductive amination [CE-LIF (APTS-HR2)], and cartridge-based capillary gel electrophoresis with rapid 8-aminonaphthalene-1,3,6-trisulfonate (ANTS) labeling, in development specifically for screening [CCGE(ANTS)].…”
Section: Resultsmentioning
confidence: 99%
“…in oligosaccharides is known to decrease their HPAE retention time (Hardy and Townsend, 1988), which explains why XG8 (devoid of fucose) has a greater retention time than XG9. Recently, McDougall and Fry (1991a) reported that XG8 does in fact elute later than XG9 on a CarboPak PA-1 anion exchange column.…”
Section: Substrate Specificity Of A-fucosidasementioning
confidence: 99%
“…4. Previously, the components and structures of N-glycans from bovine fetuin have been well characterized by chromatographic separation, HPAEC-PAD analysis, and detailed NMR studies (67)(68)(69)(70). The majority (ÏŸ80%) of the N-glycans were triantennary N-glycans with varied degrees of ␣2,6-and/or ␣2,3-sialylations at the terminus.…”
Section: Generation and Characterization Of Glycosynthase Mutants Of mentioning
confidence: 99%
“…5B). The assignment of the peaks was based on a detailed HPAEC-PAD analysis of fetuin N-glycans reported previously (67,69 (Fig. 5C).…”
Section: Generation and Characterization Of Glycosynthase Mutants Of mentioning
confidence: 99%